Plasma and cerebrospinal fluid concentrations of linezolid in neurosurgical critically ill patients with proven or suspected central nervous system infections - Luque, S.; Grau, S.; Alvarez-Lerma, F.; Ferrández, O.; Campillo, N.; Horcajada, J.P.; Basas, M.; Lipman, J.; Roberts, J.A. (International journal of antimicrobial agents, 2014)
•In these patients, linezolid demonstrated good but variable penetration into the CNS.•A 3-compartment model was used; the mean value for linezolid clearance was 16.6L/h and volume of distribution 101.3L.•To ensure all patients achieve adequate CNS concentrations the use of higher than standard doses and TDM is necessary. Linezolid is a valuable treatment option for central nervous system (CNS) infections caused by multidrug-resistant Gram-positive micro-organisms. Data regarding its penetration into the CNS have shown wide variability. The aim of this study was to describe the population pharmacokinetics of linezolid in plasma and cerebrospinal fluid (CSF) in critically ill patients with external CSF drainage and proven or suspected CNS infections. This was an observational pharmacokinetic (PK) study in 11 critically ill patients with proven or suspected CNS infection receiving linezolid. Serial blood and CSF samples were taken and were subject to population PK analysis. The median (interquartile range) of AUC0–12h was 47.6 (17.9–58.6)mgh/L in plasma and 21.1 (18.8–30.4)mgh/L in CSF, with a median CSF/plasma ratio of 0.77. At pre-dose at steady state, a strong positive correlation was observed between linezolid concentrations in CSF and plasma (Spearman's rho=0.758; P=0.011). For a minimum inhibitory concentration (MIC) of 2mg/L, the median AUC0–24h/MIC values in plasma and CSF were <80 in all patients. A three-compartment linear model was found to be most appropriate. The mean value for linezolid clearance was 16.6L/h and mean volume of distribution was 101.3L. No covariate relationships could be supported on any of the parameters. Linezolid demonstrated good penetration into the CNS but high interindividual PK variability. Administration of higher than standard doses of linezolid and therapeutic drug monitoring should therefore be considered as options to optimise linezolid dosing in critically ill patients with CNS infections.